Stereotactic Body Radiotherapy for Spinal Metastases at the Extreme Ends of the Spine: Imaging-Based Outcomes for Cervical and Sacral Metastases. Issue 5 (29th August 2018) - Zeng, K Liang; Myrehaug, Sten; Soliman, Hany; Tseng, Chia-Lin; Atenafu, Eshetu G; Campbell, Mikki; Faruqi, Salman; Lee, Young K; Ruschin, Mark; da Costa, Leodante; Yang, Victor; Spears, Julian; et al.
Abstract: Background: The unique anatomy and biomechanical features of the cervical spine and sacrum may impact treatment outcomes following spine stereotactic body radiotherapy (SBRT). Current data for spine metastases are not specific for these locations. Objective: To report imaging-based SBRT outcomes to cervical and sacral metastases. Methods: We retrospectively reviewed our prospective spine SBRT database for cervical and sacral metastases. Patients were followed at 2- to 3-mo intervals with a clinical visit and full spine magnetic resonance imaging (MRI) and we report overall survival (OS), vertebral compression fracture (VCF), and MR imaging-based local control (LC) rates. Results: Fifty-two patients and 93 treated spinal segments were identified. Fifty-six segments were within the cervical spine and 37 within the sacrum, the median follow-up was 14.4 and 19.5 mo, and the median total dose/number of fractions was 24 Gy/2, respectively. Cumulative LC at 1 and 2 yr were 94.5% and 92.7% for the cervical cohort, and 86.5% and 78.7% in the sacral cohort, respectively. Lack of posterior spinal element involvement in the cervical spine ( P  < .0001) and absence of epidural disease (hazard ratio 0.275, 95% confidence interval 0.076-0.989, P  = .048) in the sacral cohort predicted LC. Median OS was 16.3 and 28.5 mo in the cervical spine and sacrum cohorts, respectively. Two cases of sacral VCF, 1 brachial plexopathy, and 1 lumbar-sacral plexopathy were observed. CONCLUSION: Although high rates of LC were observed, strategies specific to the sacrum may require further optimization.